Refrigerants – charge limits and user safety according to the Pressure Equipment Directive, ISO 817 and PN-EN 378 - Zajączkowski, Bartosz; Hałon, Tomasz; Reszewski, Stefan (Instal, 2020)
The article presents the methodology for calculating the maximum refrigerant charge in refrigeration installations depending on refrigerants flammability and toxicity. The methodology is taken from ISO 817: 2014 and EN 378-1: 2016. Examples of calculations and examples of technical solutions are also shown, thanks to which it is possible to solve problems related to the design of multi-evaporator refrigeration installations by following the standards and engineering practice.
Keywords: refrigeration; air conditioning; safety; flammability; toxicity; standards